Fundamentals of Entrepreneurship (ENT300) : Case study Mira Cake House Kek Lapis Sarawak / Angeli Shima Eli … [et al.] - Eli, Angeli Shima; Ujang, Celine; Jonathan, Escardina Grace; Anyi, Kathryn Do; Bollhassan, Nurul Ainul Assyakirin (2019)
Mira Cake House has been publicly known in Kota Samarahan especially by the students from UiTM Kota Samarahan 1 and 2, and students from UNIMAS due to the location that is easily founded in the area. Mira Cake House products are cakes, specifically the kek lapis basah. The main problem faced by Mira Cake House is competition problem. Problems that are related to competition problem is that there are a few more cake houses in the same area which is a few minutes drive from each other's places. The other competitor set the high price compared to prices set by Mira Cake House. The price of goods become low and Mira Cake House need to face the problem. Mira Cake House had to cut the prices of all cakes to RM10 to attract customers, especially students as the price of one cake is affordable. The price set by Mira Cake House shows the quality of the business.